Looking at Painting in Florence, 13th-16th Centuries: A Learner's Handbook - Richard Peterson (Italy Edizioni Polistampa, 2018)
Illustrated handbook on Florentine painting from the Middle Ages through the Renaissance, intended to bridge the gap between the guidebook and the serious academic text, organized chronologically around the churches, cloisters, museums, and palaces that house the city's art
Santa Croce Church and Museum -- Orsanmichele -- Santa Maria del Carmine, Brancacci Chapel -- Uffizi Gallery -- Santa Maria Novella Church and Cloister -- San Marco Convent and Museum -- Santa Apollonia Refectory -- Accademia Gallery -- Santissima Annunziata Church and Cloister -- San Michele Visdomini -- Santa Felicita -- San Lorenzo -- Pitti Palace, Galleria Palatina -- Palazzo Vecchio
Keywords: Christian Antiquities (3GdBKGQ GdeSjMjIs; Painting, Italian -- Italy -- Florence; Painting, Medieval -- Italy -- Florence; Painting, Renaissance -- Italy -- Florence; History